Effect of Natural Ageing of Basmati Paddy on Physico-chemical and Textural Properties of Cooked Rice - Kaur, Jasleen; Chand, Tarsem (Journal of Agricultural Engineering, 2011)
Ageing of paddy (c.v. Basmati-386) was done for five months through storage in gunny bags (polyethylene lining), high density polyethylene (HDPE, 100 micron) and low density polyethylene (LDPE, 100 micron) bags to study rice quality. Aroma (volatile residual substance value), cooking coefficient, elongation ratio and water absorption increased markedly whereas amylose content, cooking time and solid loss in gruel decreased with the ageing of paddy. Textural properties of cooked rice like hardness, cohesiveness, springiness, gumminess and chewiness increased with ageing. All the textural properties had significant positive correlation with each other and had negative correlation with optimum cooking time. The physico-chemical properties of rice correlated well with their cooking and textural properties.